PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI (Pengurus Pergerakan Mahasiswa Islam Indonesia Rayon Alfarabi) - Kafi Achmad Rusydi; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine Knowing the influence of the organization and motivation on organizational commitment. The data used in this study are Primary data, the research population is the management of the Indonesian Islamic Student Movement organization Rayon Alfarabi while the study sample was taken from the population using sampling techniques using proportional stratified random sampling method.The results obtained using the multiple linear regression test Y = 3.102+ 0.139X1 + 0.202X2 + e, and the test from this study used the t test. The results showed that the partial variable of organizational culture and motivation had a positive effect on organizational commitment. Keywords: Organizational Culture, Motivation and Organizational Commitment